The influence of scavengers on VOC emissions in particleboards made from pine and poplar - N. A. Costa (2014)
This paper studies the performance of scavengers on Volatile Organic Compound (VOC) emissions from wood-based composites. Particleboards made from maritime pine (Pinus pinaster Ait.) and European poplar (Populus spp.) were produced with a UF resin doped with melamine and two scavengers, sodium metabisulfite and urea. VOC emission was measured according to EN ISO 16000. Particleboards made from pine present much higher total VOC (TVOC) emissions than boards made from poplar. Pine emits a higher amount of terpenes, but also aldehydes, acids and terpenoids, while poplar emits mainly acetic acid. Sodium metabisulfite showed an excellent ability to reduce aldehydes emission, which represents nearly 50 % of total emission of particleboards made from pine. When sodium metabisulfite was applied to particleboards made from poplar, reduction of TVOCs was not significant due to the low contribution of aldehydes to TVOCs. Urea presents a low reduction in TVOCs for both wood species.